The Morphometric and Hydrological Analysis of the Largest Valley Basin in the Western Plateau of Iraq - Mohammed, Maryam J.; Jawad, Laith A. (Iraqi Journal of Science, 2024)
The study was carried out to see whether it would be possible to use remote sensing and Geographic Information System (GIS) to create a morphometric geodatabase for the largest valley basin in the western Plateau (Houran Valley), Iraq. ArcGIS V.10.8 measured morphological or hydrological features using a digital elevation model (DEM). These properties are considered a crucial database for planning for dry or wet river basins and valleys, saving time, money, and resources compared to extensive regional research. A quantitative investigation of the morphological characteristics determined that the longitudinal drain density was 0.1698 km/Km2, indicative of both high soil permeability and an arid to semi-arid desert environment. The basin is in an early geomorphological stage, and the linear structures determined the design of its drainage network according to the circulation ratio of 0.08566. area’s geological structure has considerable changes in hardness, as indicated by the elongation ratio of 0.112, which would facilitate the use of water in the process of the area’s sustainable development.